Análise custo-efetivo de amplificação de ácidos nucleicos para o diagnóstico da tuberculose resistente por meio do teste Genotype®MTBDRplus - Valéria Martins Soares (2018)
Aim: Assess the mean cost and activity based cost (ABC) of the laboratory diagnosis for tuberculosis in a tertiary referral hospital and cost-effectiveness of Genotype® MTBDRplus. Materials & Methods: The cost analysis was based on two methods: mean cost and ABC. Results: The mean cost and ABC were, respectively, U$4.00/U$3.24 for bacilloscopy, U$6.73/U$5.29 for a Lowenstein-Jensen (LJ) culture, U$105.42/U$76.56 for a drug sensitivity test (DST) - proportions method (PM) in LJ, U$148.45/U$136.80 for a DST - BACTECTMMGITTM960 system (MGIT), U$11.53/U$9.89 for Xpert®MTB/RIF andU$84.21/U$48.38 for Genotype®MTBDRplus. Conclusions: The Genotype®MTBDRplus was cost-effective. The mean cost, ABC and cost-effectiveness proved to be good parameters for decision-making in the diagnosis of TB and MDR-TB. Although efforts to control the global tuberculosis (TB) epidemic have reduced their mortality and incidence, there are several predisposing factors to be controlled to reduce the disease burden. The objective of this study was to evaluate the factors associated with TB and resistant TB in patients treated at a tertiary referral hospital. It is a cross-sectional study in which the variables used were grouped into: sociodemographic, behavioral and clinical characteristics. The endpoint considered to verify the association between TB and explanatory variables was the treatment prescribed for TB. To assess the association between resistant TB and the same explanatory variables, the change in treatment for MDR-TB was considered. Alcoholism, suggestive chest X-ray and the presence of pulmonary cavitations were risk factors for TB and the presence of comorbidities was associated with the disease. TBMDR was associated with previous treatment and the presence of cavitations. Despite important progress in the fight against TB, a set of articulated actions that include measures of social protection and patient support are needed.